Macroeconomic policy in a small open-economy when government budget deficits are financed by printing money - Murray, S (Economic & Social Studies, 1980)
This paper presents a dynamic macroeconomic model of a small open economy (SOE) in which government budget deficits are financed by printing money, the dynamics arising from a stock-adjustment approach to capital movements and the government's budget constraint. Stability conditions and the medium-term policy multipliers are derived. Fiscal policy raises income in the medium run but an expansionary monetary policy by open market operations (resulting in a fall in the parametric bond stock) reduces income. There are some striking symmetries between fiscal and monetary policies: a one-unit increase in government spending has exactly the same effect on steady-state income, the money stock, and the total bond stock, as a one-unit rise in the stock of government bond.
Keywords: Small open economies (SOE); Ireland